Knowledge Management Evaluation in Oil and Gas Company Using Analytic Hierarchy Process - Firdha Ruvania; Tanika D Sofianti; Ivanos Tertiana (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2015)
In today’s competitive business environment, competition between organizations has become strict and more competitive. Oil and Gas Company is a learning organization that manages knowledge for implementing Knowledge Management (KM) as company intangible asset in order to reach higher competitive advantage. The investment in KM needs to be evaluated to assure the advantage obtained from the investment. The objective of this study is to evaluate knowledge management performance by comparing and ranking each division to find division that represents the most desirable performance to the least performance. The methodology used to evaluate is Analytic Hierarchy Process (AHP). The AHP arranges the decision problem into a hierarchy of more easily comprehended. This research adopts SECI model as a criteria that correlated to KM performance. In order to identify the area for improvements by means of determine the differences between division, gap analysis was conducted. Prioritize of criteria socialization (37.68%), internalization (23.63%), combination (23.61%), and externalization (15.08%). The result of division with highest weight of KM performance is planning and the lowest is financial. Financial division needs to improve the overall SECI process by increasing interaction between team members, routine progress reports and also verbalizing knowledge based on documents. A case study in an oil and gas company was conducted to demonstrate how to evaluate KM using AHP.